A STUDY ON EXPORT TRADE OF FLOWERS IN INDIA CONCERNING TAMILNADU - Shahila .S; Raj, P. Antony; M Jegathish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Our country considers Floriculture a hi-tech industry due to its diverse eco-geographical regions and varied agroclimatic conditions. India is well-suited for growing all kinds of flowers throughout the year. A researcher conducted a study to analyse the factors behind the export of flower businesses in the Thovalai region, a prominent centre for flower production and trade. The researcher designed a comprehensive interview schedule based on previous studies and research objectives and selected 150 exporters from the Thovalai flower market to collect the required data. The study revealed that several factors influence the export of flower business in the study area.